Fe-Co micron alloy catalyst as well as preparation method and application thereof

Through the preparation method of Fe-Co micron alloy catalyst, the size and morphology of the alloy are adjusted by dispersant and capping agent, and a high dispersed oxygen vacancy is formed through the H2 reduction step, which solves the problem of low carbon dioxide methanation reaction efficiency at low temperatures and achieves efficient and stable CO2 methanation.

CN119657147AActive Publication Date: 2025-03-21WUHAN INST OF TECH +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411826807.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The prior art has low efficiency in carbon dioxide methanation reaction at low temperatures, unclear correlation of catalyst structure-catalytic properties, and the active sites of nano alloy catalysts increase, stability and recovery capabilities are insufficient during the preparation process.

Method used

The Fe-Co micron alloy catalyst is used to regulate the size of the metal alloy by dispersing agent, capping agent and reaction time. The difference in metal redox properties and the metal arrangement method in the alloy step are used to achieve high dispersed oxygen vacancies in the H2 reduction step, increasing the active site of the catalyst.

Benefits of technology

It has achieved efficient methanation of CO2, and the catalyst has a large specific surface area and high stability. The metal active sites around oxygen vacancies in the Fe-Co micro-alloy structure can efficiently activate H2, significantly improving the selectivity of CH4.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657147A_ABST
    Figure CN119657147A_ABST
Patent Text Reader

Abstract

The invention relates to the field of carbon dioxide catalytic conversion, in particular to a Fe-Co micron alloy catalyst and a preparation method and application thereof.The preparation method includes the steps that firstly, a metal salt solution is subjected to hydrazine hydrate reduction treatment under the strong alkaline condition, and the dosage and reaction time of a cyclohexane dispersing agent and an end-capping reagent PEG-400 are adjusted to prepare Fe-Co micron alloy; and drying in air at room temperature to oxidize the surfaces of alloy particles, and then carrying out H2 reduction treatment to obtain the Fe-Co micron alloy with high-dispersion oxygen vacancies on the surface, and the Fe-Co micron alloy can be directly used for CO2 hydrogenation reaction without subsequent treatment. The catalyst is easy to synthesize and good in stability, the prepared catalyst can achieve methane selectivity of more than 99% in a CO2 hydrogenation reaction, and the CO2 conversion rate in a high-pressure reaction kettle can reach 62.5% within 1 h.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalytic conversion of carbon dioxide, and in particular to a Fe-Co micron alloy catalyst and a preparation method and application thereof. Background Art

[0002] Carbon dioxide is not only the main source of greenhouse gas emissions, but also plays a key role in the earth's carbon cycle. However, due to its chemical stability, the conversion and utilization of carbon dioxide has always been a challenge. Among the many conversion pathways, the methanation reaction of carbon dioxide has attracted special attention because it can directly convert carbon dioxide into methane, a clean fuel. However, there are still many problems to be solved in CO2 methanation. First, the cleavage of the carbon-oxygen bond (CO) in the carbon dioxide molecule is a major challenge, resulting in the low efficiency of the carbon dioxide methanation reaction at low temperatures (≤350℃). Although the use of cost-effective nickel-based catalysts can improve the methanation performance at low temperatures (~300℃), there are still few reports on achieving higher carbon dioxide conversion rates at lower temperatures (≤240℃), and the structure-catalytic performance correlation of the catalyst is not well understood. Second, the content and distribution of oxygen vacancies and hydroxyl groups in the catalyst support affect the methanation performance, but the exact underlying mechanisms controlling these effects have not been consistently documented.

[0003] Transition metal nanoalloys have many applications in the catalytic conversion of CO2, but too small nanoparticles weaken the CO2 adsorption capacity, resulting in the production of more byproduct CO. In addition, how to increase the active sites of alloy catalysts during the preparation process, improve the stability and recovery ability of the catalyst, and achieve high selectivity and high conversion rate are problems that need to be solved at present. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a Fe-Co micron alloy catalyst and a preparation method and application thereof. The present invention regulates the size of the metal alloy by means of a dispersant, a capping agent and a reaction time, and utilizes the difference in metal redox properties and the metal arrangement in the alloying step to achieve the formation of highly dispersed oxygen vacancies in the H2 reduction step.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A method for preparing a Fe-Co micron alloy catalyst comprises the following steps:

[0007] Soluble cobalt salt and soluble iron salt are used as raw materials, cyclohexane is used as a dispersant, polyethylene glycol 400 is used as a capping agent, the shape of alloy particles is changed by controlling the growth rates of different crystal faces, the mixture is dissolved in water, and after heating, hydrazine hydrate is added under alkaline conditions to reduce the soluble cobalt salt and the soluble iron salt to obtain a black-gray mixed solution, and a solid product in the black-gray mixed solution is separated to obtain Fe-Co micron alloy particles.

[0008] The Fe-Co micron alloy particles are oxidized on the surface and then subjected to H2 reduction treatment to obtain a Fe-Co micron alloy catalyst with highly dispersed oxygen vacancies.

[0009] The invention uses soluble cobalt salt and soluble iron salt as raw materials, cyclohexane as a dispersant, polyethylene glycol 400 as a capping agent, and uses hydrazine hydrate to perform reduction treatment on the soluble metal salt to obtain Fe-Co micron alloy particles. The surfaces of the Fe-Co micron alloy particles are oxidized and then subjected to H2 reduction treatment to obtain Fe-Co micron alloy catalysts with highly dispersed oxygen vacancies. The dispersant cyclohexane used in the invention can efficiently disperse the alloy particles and promote orderly arrangement of metals between the alloy particles. The polyethylene glycol 400 changes the shape of the alloy particles by regulating the growth rates of different crystal faces. Polyethylene glycols of different molecular weights have different viscosities and polymer chain lengths, thereby affecting the reaction in the solution. Polyethylene glycols with higher molecular weights will excessively inhibit the growth of the alloy particles. Finally, the difference in metal redox performance and the metal arrangement mode in the synthesis step are used to realize the formation of highly dispersed oxygen vacancies in the H2 reduction step, thereby increasing the active sites of the catalyst and realizing efficient methanation of CO2.

[0010] The hydrazine hydrate reduction method adopted in the present invention has the following advantages: 1. the process is simple and the requirements for experimental equipment are low; 2. the size and morphology of micron particles are easy to control; 3. the reduction product is convenient for subsequent treatment; 4. other reducing agents have the problems of complex reduction process, insufficient reduction ability, need to add a coordination agent, and are not conducive to subsequent treatment.

[0011] In a preferred embodiment of the present invention, the molar ratio of cobalt to iron in the soluble cobalt salt and the soluble iron salt is 3 to 9:1.

[0012] In a preferred embodiment of the present invention, the dosage ratio of cyclohexane to soluble cobalt salt is 1 mL: 0.6 mmol~14 mmol, the dosage ratio of cyclohexane to polyethylene glycol 400 is 1 mL: 3.4 g~21.5 g, and the dosage ratio of water to polyethylene glycol 400 is 1 mL: 0.05 g~0.34 g. Too little or excessive dosage of the capping agent will result in the formation of a large number of nanosheets with irregular morphology.

[0013] In a preferred embodiment of the present invention, the usage ratio of the soluble cobalt salt to the hydrazine hydrate is 1 mL: 0.02 mmol to 0.5 mmol, and the mass concentration of the hydrazine hydrate is 75% to 85%.

[0014] In a preferred embodiment of the present invention, the hydrothermal reaction temperature is 70°C to 85°C, the hydrothermal reaction time is 6h to 10h, and sodium hydroxide agent hydrazine hydrate is added at 70°C to 85°C: ① the original solvent is mixed evenly; ② the reaction speed is accelerated, and a part of the N2 generated by the reduction reaction is released to avoid excessive gas pressure in the polytetrafluoroethylene reactor; ③ too high a reaction temperature is more dangerous.

[0015] In a preferred embodiment of the present invention, the H2 reduction treatment temperature is 280°C to 400°C, and the reduction treatment time is 1h to 3h.

[0016] In a preferred embodiment of the present invention, the soluble cobalt salt is cobalt chloride hexahydrate, and the soluble iron salt is ferrous sulfate heptahydrate.

[0017] Another object of the present invention is to provide a Fe-Co micron alloy catalyst prepared by the preparation method described in any one of the above claims.

[0018] The third object of the present invention is to provide an application of the above-mentioned Fe-Co micron alloy catalyst in CO2 hydrogenation reaction.

[0019] The application method is: introducing a mixed gas of CO2 and H2 into the Fe-Co micron alloy catalyst for reaction, the reaction temperature is 160°C to 280°C, the reaction pressure is 3MPa to 6MPa, the reaction time is 60min to 70min, and the volume ratio of CO2 to H2 in the mixed gas is 1:3 to 6.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention uses soluble cobalt salt and soluble iron salt as raw materials, cyclohexane as a dispersant, polyethylene glycol 400 as a capping agent, and uses hydrazine hydrate to reduce the soluble metal salt to obtain Fe-Co micron alloy particles. The Fe-Co micron alloy surface is oxidized and then subjected to H2 reduction treatment to obtain a Fe-Co micron alloy catalyst with highly dispersed oxygen vacancies. The dispersant cyclohexane used in the present invention can efficiently disperse the alloy particles and promote the orderly arrangement of the metals between the alloy particles. Polyethylene glycol 400 changes the shape of the alloy particles by regulating the growth rates of different crystal faces. Polyethylene glycols of different molecular weights have different viscosities and polymer chain lengths, thereby affecting the reaction in the solution. Polyethylene glycols with higher molecular weights will excessively inhibit the growth of the alloy particles. Finally, the difference in metal redox properties and the metal arrangement in the synthesis step are utilized to realize the formation of highly dispersed oxygen vacancies in the H2 reduction step, thereby increasing the active sites of the catalyst and realizing efficient methanation of CO2.

[0022] 2. The Fe-Co micron alloy catalyst of the present invention has a large specific surface area and high stability. The efficiently dispersed oxygen vacancies in the Fe-Co micron alloy are helpful for CO2 adsorption, which is beneficial to the methanation reaction. The metal active sites around the oxygen vacancies in the Fe-Co micron alloy structure can efficiently activate H2. The hydrogen overflow effect makes the CO bonds adsorbed on the Fe-Co micron alloy easier to break. At the same time, the highly dispersed vacancies effectively inhibit CC coupling and significantly improve the selectivity of CH4.

[0023] 3. The Fe-Co micron alloy with highly dispersed oxygen vacancies on the surface prepared by the present invention can be directly used in CO2 hydrogenation reaction without subsequent treatment. The catalyst is easy to synthesize, has good stability, and has low material price. The catalyst prepared by the present invention can achieve a methane selectivity greater than 99% in the CO2 hydrogenation reaction, and the CO2 conversion rate in the high-pressure reactor can reach 62.5% in 1 hour, which has a prospect for development in the direction of industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Microscopic morphology of the catalysts prepared in Examples 1 to 2 of the present invention and Comparative Example 1.

[0025] Figure 2 The X-ray diffraction patterns of the catalysts prepared in Examples 1 to 2 of the present invention and Comparative Example 1 are shown.

[0026] Figure 3 This is a hydrogen temperature-programmed reduction diagram of the catalysts prepared in Examples 1 to 2 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0027] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0029] Example 1

[0030] A method for preparing a Fe-Co micron alloy catalyst comprises the following steps:

[0031] (1) 5.36 g of cobalt chloride hexahydrate, 0.695 g of ferrous sulfate heptahydrate, 4 mL of cyclohexane, and 34.4 g of polyethylene glycol 400 were dissolved in 250 mL of deionized water, wherein the molar ratio of cobalt to iron was 9:1. When heated to 80° C., 12.35 g of sodium hydroxide and 106 mL of 80% hydrazine hydrate were added to obtain a black-gray mixed solution.

[0032] (2) placing the black-gray mixed solution in a polytetrafluoroethylene reactor and subjecting it to reduction treatment at 80° C. for 6 h, and after cooling, using a permanent magnet bar to preliminarily separate the solid product in the black-gray mixed solution to obtain Fe—Co micron alloy particles.

[0033] (3) The solid product was washed five times with deionized water and then three times with anhydrous ethanol, and dried at room temperature under air conditions to promote surface oxidation of the micro-alloy. The dried Fe-Co micro-alloy was subjected to H2 reduction treatment at 300°C for 1 hour to obtain a Fe-Co micro-alloy catalyst.

[0034] Example 2

[0035] A method for preparing a Fe-Co micron alloy catalyst comprises the following steps:

[0036] (1) Cobalt chloride hexahydrate, ferrous sulfate heptahydrate, 4 mL of cyclohexane, and 34.4 g of polyethylene glycol 400 were dissolved in 250 mL of deionized water, wherein the molar ratio of cobalt to iron was 3:1. When heated to 80° C., 12.35 g of sodium hydroxide and 106 mL of 80% hydrazine hydrate were added to obtain a black-gray mixed solution.

[0037] (2) placing the black-gray mixed solution in a polytetrafluoroethylene reactor and subjecting it to reduction treatment at 80° C. for 6 h, and after cooling, using a permanent magnet bar to preliminarily separate the solid product in the black-gray mixed solution to obtain Fe—Co micron alloy particles.

[0038] (3) The solid product was washed five times with deionized water and then three times with anhydrous ethanol, and dried at room temperature under air conditions to promote surface oxidation of the micro-alloy. The dried Fe-Co micro-alloy was subjected to H2 reduction treatment at 300°C for 1 hour to obtain a Fe-Co micro-alloy catalyst.

[0039] Example 3

[0040] A method for preparing a Fe-Co micron alloy catalyst comprises the following steps:

[0041] (1) Cobalt chloride hexahydrate, ferrous sulfate heptahydrate, 4 mL of cyclohexane, and 34.4 g of polyethylene glycol 400 were dissolved in 250 mL of deionized water, wherein the molar ratio of cobalt to iron was 6:1. When heated to 80° C., 12.35 g of sodium hydroxide and 106 mL of 80% hydrazine hydrate were added to obtain a black-gray mixed solution.

[0042] (2) placing the black-gray mixed solution in a polytetrafluoroethylene reactor and subjecting it to reduction treatment at 80° C. for 6 h, and after cooling, using a permanent magnet bar to preliminarily separate the solid product in the black-gray mixed solution to obtain Fe—Co micron alloy particles.

[0043] (3) The solid product was washed five times with deionized water and then three times with anhydrous ethanol, and dried at room temperature under air conditions to promote surface oxidation of the micro-alloy. The dried Fe-Co micro-alloy was subjected to H2 reduction treatment at 300°C for 1 hour to obtain a Fe-Co micro-alloy catalyst.

[0044] Example 4

[0045] A method for preparing a Fe-Co micron alloy catalyst comprises the following steps:

[0046] (1) 5.36 g of cobalt chloride hexahydrate, 0.695 g of ferrous sulfate heptahydrate, 1.6 mL of cyclohexane, and 13.76 g of polyethylene glycol 400 were dissolved in 100 mL of deionized water, wherein the molar ratio of cobalt to iron was 9:1. When heated to 80° C., 12.35 g of sodium hydroxide and 42.4 mL of 80% hydrazine hydrate were added to obtain a black-gray mixed solution.

[0047] (2) placing the black-gray mixed solution in a polytetrafluoroethylene reactor and subjecting it to reduction treatment at 70° C. for 10 h, and after cooling, using a permanent magnet bar to preliminarily separate the solid product in the black-gray mixed solution to obtain Fe—Co micron alloy particles.

[0048] (3) The solid product was washed five times with deionized water and then three times with anhydrous ethanol, and dried at room temperature under air conditions to promote oxidation of the micro-alloy surface. The dried Fe-Co micro-alloy was subjected to H2 reduction treatment at 280°C for 3 hours to obtain a Fe-Co micro-alloy catalyst.

[0049] Example 5

[0050] A method for preparing a Fe-Co micron alloy catalyst comprises the following steps:

[0051] (1) 5.36 g of cobalt chloride hexahydrate, 0.695 g of ferrous sulfate heptahydrate, 2.4 mL of cyclohexane, and 24.4 g of polyethylene glycol 400 were dissolved in 180 mL of deionized water, wherein the molar ratio of cobalt to iron was 9:1. When heated to 80° C., 12.35 g of sodium hydroxide and 65 mL of 80% hydrazine hydrate were added to obtain a black-gray mixed solution.

[0052] (2) placing the black-gray mixed solution in a polytetrafluoroethylene reactor and subjecting it to reduction treatment at 85° C. for 8 h, and after cooling, using a permanent magnet bar to preliminarily separate the solid product in the black-gray mixed solution to obtain Fe-Co micron alloy particles.

[0053] (3) The solid product was washed five times with deionized water and three times with anhydrous ethanol, and dried at room temperature under air conditions to promote surface oxidation of the micro-alloy. The dried Fe-Co micro-alloy was subjected to H2 reduction treatment at 400°C for 2h to obtain a Fe-Co micro-alloy catalyst.

[0054] Comparative Example 1

[0055] A method for preparing a Fe-Co micron alloy catalyst comprises the following steps:

[0056] (1) Cobalt chloride hexahydrate, ferrous sulfate heptahydrate, 4 mL of cyclohexane, and 34.4 g of polyethylene glycol 400 were dissolved in 250 mL of deionized water, wherein the molar ratio of cobalt to iron was 1:3. When heated to 80° C., 12.35 g of sodium hydroxide and 106 mL of 80% hydrazine hydrate were added to obtain a black-gray mixed solution.

[0057] (2) placing the black-gray mixed solution in a polytetrafluoroethylene reactor and subjecting it to reduction treatment at 80° C. for 6 h, and after cooling, using a permanent magnetic rod to preliminarily separate the solid product in the black-gray mixed solution.

[0058] (3) The solid product was washed five times with deionized water and then three times with anhydrous ethanol, and dried at room temperature under air conditions to promote surface oxidation of the micro-alloy. The dried Fe-Co micro-alloy was subjected to H2 reduction treatment at 300°C for 1 hour to obtain a Fe-Co micro-alloy catalyst.

[0059] In a high-pressure reactor equipped with magnetic stirring, add 100 mg of catalyst and introduce a mixture of CO2 and H2. After reaching the reaction temperature, take samples at regular intervals to detect the content of each component in the gas phase by gas chromatography (GC-FID / TCD), and calculate the CH4 selectivity and CO2 conversion rate:

[0060]

[0061] Application Example 1

[0062] 100 mg of Fe-Co micron alloy (1:3) was placed in a reactor, and a CO2:H2 (3:1) mixed gas was introduced. The reaction conditions were adjusted to 280°C and 6 MPa. The reaction was carried out for 60 minutes. The CO2 and CH4 contents were measured and the CO2 conversion rate was calculated to be 30.9% and the CH4 selectivity was 80.7%.

[0063] Application Example 2

[0064] 100 mg of Fe-Co micron alloy (1:3) was placed in a reactor, and a CO2:H2 (1:3) mixed gas was introduced. The reaction conditions were adjusted to 280°C and 6 MPa. The reaction was carried out for 60 minutes. The CO2 and CH4 contents were measured and the CO2 conversion rate was calculated to be 20.7% and the CH4 selectivity was 96.1%.

[0065] Application Example 3

[0066] 100 mg of Fe-Co micron alloy (1:9) was placed in a reactor, and a CO2:H2 (1:3) mixed gas was introduced. The reaction conditions were adjusted to 280°C and 6 MPa. The reaction was carried out for 60 minutes. The CO2 and CH4 contents were measured and the CO2 conversion rate was calculated to be 35.8% and the CH4 selectivity was 99%.

[0067] Application Example 4

[0068] 100 mg of Fe-Co micron alloy (1:9) was placed in a reactor, and a CO2:H2 (1:3) mixed gas was introduced. The reaction conditions were adjusted to 160°C and 6 MPa. The reaction was carried out for 60 minutes. The CO2 and CH4 contents were measured and the CO2 conversion rate was calculated to be 4.3% and the CH4 selectivity was 98.7%.

[0069] Application Example 5

[0070] 100 mg of Fe-Co micron alloy (1:9) was placed in a reactor, and a CO2:H2 (1:3) mixed gas was introduced. The reaction conditions were adjusted to 200°C and 6 MPa. The reaction was carried out for 60 minutes. The CO2 and CH4 contents were measured and the CO2 conversion rate was calculated to be 9.1% and the CH4 selectivity was 99.1%.

[0071] Application Example 6

[0072] 100 mg of Fe-Co micron alloy (1:9) was placed in a reactor, and a CO2:H2 (1:3) mixed gas was introduced. The reaction conditions were adjusted to 240°C and 6 MPa. The reaction was carried out for 60 minutes. The CO2 and CH4 contents were measured and the CO2 conversion rate was calculated to be 18.7% and the CH4 selectivity was 98.9%.

[0073] Application Example 7

[0074] 100 mg of Fe-Co micron alloy (1:9) was placed in a reactor, and a CO2:H2 (1:3) mixed gas was introduced. The reaction conditions were adjusted to 280°C and 3 MPa. The reaction was carried out for 60 minutes. The CO2 and CH4 contents were measured and the CO2 conversion rate was calculated to be 53.1% and the CH4 selectivity was 93.6%.

[0075] Application Example 8

[0076] 100 mg of Fe-Co micron alloy (1:9) was placed in a reactor, and a CO2:H2 (1:3) mixed gas was introduced. The reaction conditions were adjusted to 280°C and 4 MPa. The reaction was carried out for 60 minutes. The CO2 and CH4 contents were measured and the CO2 conversion rate was calculated to be 45.5% and the CH4 selectivity was 94.8%.

[0077] Application Example 9

[0078] 100 mg of Fe-Co micron alloy (1:9) was placed in a reactor, and a CO2:H2 (1:3) mixed gas was introduced. The reaction conditions were adjusted to 280°C and 5 MPa. The reaction was carried out for 60 minutes. The CO2 and CH4 contents were measured and the CO2 conversion rate was calculated to be 38.6% and the CH4 selectivity was 98.4%.

[0079] Application Example 10

[0080] 100 mg of Fe-Co micron alloy (1:9) was placed in a reactor, and a CO2:H2 (1:6) mixed gas was introduced. The reaction conditions were adjusted to 280°C and 6MPa. The reaction was carried out for 60 minutes. The CO2 and CH4 contents were measured and the CO2 conversion rate was calculated to be 62.5% and the CH4 selectivity was 96%.

[0081] Results Analysis

[0082] Table 1 Test results of application examples 1 to 10

[0083]

[0084]

[0085] As can be seen from Table 1, the CO2 conversion rate increases with the increase of reaction temperature, while the effect on methane selectivity is relatively low; the CO2 conversion rate decreases with the increase of reaction pressure, but at the same time, the methane selectivity is significantly improved. The CO2 conversion rate increases significantly with the increase of the proportion of H2 in the mixed gas, but at the same time, the methane selectivity decreases slightly. The metal ratio in the Fe-Co micron alloy also has a great influence on the CO2 conversion rate and CH4 selectivity. The CO2 methanation effect is best when Fe:Co is 1:9. Combined with the above application implementation data analysis, the Fe-Co micron alloy still has a high CH4 selectivity and CO2 conversion rate when the temperature and pressure and other related parameters change greatly.

[0086] Figure 1 The morphology of the Fe-Co micro alloy catalysts prepared in different Fe-Co ratios in Examples 1 to 2 of the present invention and Comparative Example 1 shows that the morphology of the catalyst changes significantly according to the amount of ferrous sulfate heptahydrate and cobalt chloride hexahydrate used. It can be clearly seen that the Fe-Co particle size increases significantly with the increase of its Co content, and the structure changes from cubic to flower rod-shaped. At the same time, the crystals mainly grow along the rod-shaped directions. The results show that the catalyst size and morphology are successfully regulated.

[0087] Figure 2 The X-ray diffraction (XRD) diagrams of the catalysts prepared in Examples 1 to 2 of the present invention and Comparative Example 1 are consistent with the characteristic peaks of the standard PDF card (PDF#48-1816Co3Fe7, PDF#50-0795Co7Fe3, PDF#15-0806Co), indicating the successful synthesis of the Fe-Co micro alloy catalyst. In addition, the positions of the characteristic peaks of the catalysts before and after the reaction are consistent, and the catalysts before and after the surface reaction are the same substance. The change in peak intensity is mainly due to the further reduction during the hydrogenation process, resulting in an increase in oxygen vacancies in the catalyst.

[0088] Figure 3The hydrogen temperature programmed reduction (H2-TPR) diagram of the catalyst prepared in Examples 1 to 2 of the present invention and Comparative Example 1 shows that the hydrogen consumption is significantly lower than that in 3:1 when the Fe:Co ratio is 1:3 and 1:9. Because Fe-Co micron particles with a higher Co content are more difficult to oxidize, less hydrogen is consumed during the reduction process, resulting in fewer surface oxygen vacancies after reduction, effectively inhibiting CC coupling, and thus higher CH4 selectivity. When Fe:Co is 1:9, the reduction peak appears at a lower temperature during the reduction process than when Fe:Co is 1:3, indicating that the micron alloy is easier to reduce when Fe:Co is 1:9, and the advantage is obvious when the reaction temperature is 280°C, so the CO2 conversion rate is higher when Fe:Co is 1:9.

[0089] In summary, the present invention uses soluble cobalt salt and soluble iron salt as raw materials, cyclohexane as dispersant, polyethylene glycol 400 as end-capping agent, and uses hydrazine hydrate to reduce the soluble metal salt to obtain Fe-Co micron alloy particles, and then performs H2 reduction treatment to obtain Fe-Co micron alloy catalyst with highly dispersed oxygen vacancies. The dispersant cyclohexane used in the present invention can efficiently disperse the alloy particles and promote the orderly arrangement of the metals between the alloy particles. Polyethylene glycol 400 changes the shape of the alloy particles by regulating the growth rate of different crystal faces. PEGs of different molecular weights have different viscosities and polymer chain lengths, thereby affecting the reaction in the solution. Polyethylene glycol with a higher molecular weight will excessively inhibit the growth of alloy particles. Finally, the difference in metal redox properties and the arrangement of metals in the synthesis step are used to achieve the formation of highly dispersed oxygen vacancies in the H2 reduction step, thereby increasing the active sites of the catalyst and achieving efficient methanation of CO2. The Fe-Co micron alloy catalyst of the present invention has a large specific surface area and high stability, with a specific surface area of ​​284m 2 / g~1952m 2 / g. Increasing the amount of metal cobalt salt during the synthesis process will increase the size of the alloy particles and reduce the specific surface area accordingly. The Fe-Co micron alloy catalyst still has 90% catalytic activity after 4 cycles. The efficiently dispersed oxygen vacancies in the Fe-Co micron alloy are conducive to CO2 adsorption, which is beneficial to the methanation reaction. The metal active sites around the oxygen vacancies in the Fe-Co micron alloy structure can efficiently activate H2. The hydrogen overflow effect makes the CO bonds adsorbed on the Fe-Co micron alloy easier to break. At the same time, the highly dispersed vacancies effectively inhibit CC coupling and significantly improve the selectivity of CH4.

[0090] It should be noted that when the present invention relates to a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundant description, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments. Therefore, the attached protection scope is intended to be interpreted as including the preferred embodiment and all changes and modifications that fall within the scope of the present invention.

[0091] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention belong to the protection scope of the present invention, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a Fe-Co micron alloy catalyst, characterized in that: The following steps are involved: Soluble cobalt salt and soluble iron salt are used as raw materials, cyclohexane is used as a dispersant, and polyethylene glycol 400 is used as a capping agent, which are mixed and dissolved in water, and after heating, hydrazine hydrate is added under alkaline conditions to reduce the soluble cobalt salt and the soluble iron salt to obtain a mixed solution, and a solid product in the mixed solution is separated to obtain Fe-Co micron alloy particles; The Fe-Co micron alloy particles are oxidized on the surface and then subjected to H2 reduction treatment to obtain a Fe-Co micron alloy catalyst with highly dispersed oxygen vacancies.

2. The method for preparing the Fe-Co micron alloy catalyst according to claim 1, characterized in that: The molar ratio of cobalt to iron in the soluble cobalt salt and the soluble iron salt is 3 to 9:

1.

3. The method for preparing the Fe-Co micron alloy catalyst according to claim 1, characterized in that: The usage ratio of cyclohexane to soluble cobalt salt is 1 mL: 0.6 mmol to 14 mmol, the usage ratio of cyclohexane to polyethylene glycol 400 is 1 mL: 3.4 g to 21.5 g, and the usage ratio of water to polyethylene glycol 400 is 1 mL: 0.05 g to 0.34 g.

4. The method for preparing the Fe-Co micron alloy catalyst according to claim 1, characterized in that: The usage ratio of hydrazine hydrate to soluble cobalt salt is 1mL: 0.02mmol~0.5mmol.

5. The method for preparing the Fe-Co micron alloy catalyst according to claim 1, characterized in that: The heating temperature is 70°C to 85°C, and the reduction treatment time after adding hydrazine hydrate is 6h to 10h.

6. The method for preparing a Fe-Co micron alloy catalyst according to claim 1, characterized in that: The H2 reduction treatment temperature is 280°C to 400°C, and the H2 reduction treatment time is 1h to 3h.

7. The method for preparing a Fe-Co micron alloy catalyst according to claim 1, characterized in that: The soluble cobalt salt is cobalt chloride hexahydrate, and the soluble iron salt is ferrous sulfate heptahydrate.

8. An Fe-Co micron alloy catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the Fe-Co micro alloy catalyst according to claim 8 in CO2 hydrogenation reaction.

10. The use according to claim 9, characterized in that: A mixed gas of CO2 and H2 is introduced into the Fe-Co micron alloy catalyst for reaction. The reaction temperature is 160°C to 280°C, the reaction pressure is 3MPa to 6MPa, the reaction time is 60min to 70min, and the volume ratio of CO2 to H2 in the mixed gas is 1:3 to 6.

Citation Information

Patent Citations

  • One-step synthesis of ethylene by taking carbon dioxide and water or methanol as raw materials

    CN103145518A

  • Controllable preparation method of ferrocobalt magnetic nanoparticles with various morphologies and high saturation magnetic induction intensity

    CN108723383A

  • Catalyst for carbon dioxide hydrogenation methanation reaction as well as preparation method and application thereof

    CN113842919A

  • Method for converting carbon dioxide into methane through metal hydride

    CN114105723A

  • Catalyst for preparing C2 + alcohol through CO2 hydrogenation as well as preparation method and application of catalyst

    CN117019167A